Penggunaan Ayat al-Qur’an dalam Pengobatan Ruqyah Ustadz Supriandi di Desa Bontorannu Kajang Sulawesi Selatan - Irsyad, Muhammad; Khirfatul Jannah; Najmuddin Abd Shafa (Program Studi Ilmu Al-Quran dan Tafsir, 2024)
The research aims to find out and explain the method and process of ruqyah using verses from the Koran and the impact of ruqyah treatment on the health of patients who seek treatment from Ustadz Supriandi. This research uses qualitative methods and includes field research using the living Qur'an approach. research location in Bontorannu Village, Kajang, South Sulawesi. The data source consists of the main informant, namely Ustadz Supriandi, and secondary informants, namely patients who seek treatment from Ustadz Supriandi. The results of the research revealed that Ustadz Supriandi used water and touch methods in his treatment. The process is carried out in three stages, namely pre-treatment, treatment process and post-treatment. The results of this research show a change in patients seeking treatment from Ustadz Supriandi. It is hoped that the implications of the research can be used as reference material and increase readers' knowledge about Al-Qur'anic medicine, especially how the Al-Qur'an lives and is practiced in society by its adherents.